The Growth In Government Domestic Debt : Changing Burdens And Risks - Hanson, James A., 1940- 1940- (The World Bank, 2007)
This paper analyzes the recent growth of government domestic debt, including central bank debt, using a new data base on government domestic debt in developing countries with large, open financial systems. On average, government domestic debt grew much faster than GDP between 1994 and 2004 and became larger than foreign debt. The rapid growth of domestic debt reflects financial crises, the growth of central bank debt and the greater attractiveness to governments of issuing domestic debt as well as the recent increase in demands for it. Both its attractiveness and the increased demands for it reflect the current benign international environment to some degree. The main risk of government debt, domestic or foreign, remains its overall size relative to a country's fiscal, financial, and political institutions. While government domestic debt can help the domestic private capital market, large domestic debt, like large external debt, has risks. For example, there can be "sudden stops" in the demand for domestic debt as well as in foreign lending. Governments need to be aware of the risks and burdens in domestic debt issue-crowding out small borrowers, transferring risks to banks when issuing longer maturity, fixed-interest domestic debt and reducing returns, and imposing risks on holders of pensions, annuities, and life insurance policies. Growth of central bank debt can divert central banks from pursuit of the objective of price stability